KERAGAMAN GENETIK MUTAN M-2 CABAI MERAH KERITING (Capsicum annuum L.) BERDASARKAN PENANDA RAPD - Rosmaina Rosmaina; Dedi Mulyadi; Rita Elfianis; Zulfahmi Zulfahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Chili is an important horticultural plant in Indonesia. This research aims to carry out RAPD analysis on Mutant M2 of chili pepper (Capsicum annuum L.). Six M2 genotypes of chili irradiated by gamma ray and control plants were amplified by 16 random primers. The amplification results of M2 chili with 16 primers produced 118 loci, with fragment sizes ranging from 150-2000 bp. The number of polymorphic loci was 96 loci and the percentage of polymorphic loci was 83.23%. The DNA fragment polymorphism produced in this research was relatively high and it showed that the gamma ray mutagen applied produced high chili genetic diversity. The value of genetic similarity between control plants and mutant plants ranged from 0.7474 to 0.4874. UPGMA dendogram classified seven genotypes tested into three groups, the first group consisted of mutants R2U6 and R2U17, the second group was mutants R1U14 and R1U17, and the third group was mutants R2U8, mutants R2U2 and control plants. The finding of this research can be used as a basic selection of genetic material for chili’s breeding in the future.